Production of full-length soluble Plasmodium falciparum RH5 protein vaccine using a Drosophila melanogaster Schneider 2 stable cell line system - Hjerrild, K; Jin, J; Wright, K; Brown, R; Marshall, J; Labbe, G; Silk, S; Cherry, C; Clemmensen, S; Jørgensen, T; Illingworth, J; Alanine, D; et al. (Nature Publishing Group, 2016)
The Plasmodium falciparum reticulocyte-binding protein homolog 5 (PfRH5) has recently emerged as a leading candidate antigen against the blood-stage human malaria parasite. However it has proved challenging to identify a heterologous expression platform that can produce a soluble protein-based vaccine in a manner compliant with current Good Manufacturing Practice (cGMP). Here we report the production of full-length PfRH5 protein using a cGMP-compliant platform called ExpreS2, based on a Drosophila melanogaster Schneider 2 (S2) stable cell line system. Five sequence variants of PfRH5 were expressed that differed in terms of mutagenesis strategies to remove potential N-linked glycans. All variants bound the PfRH5 receptor basigin and were recognized by a panel of monoclonal antibodies. Analysis following immunization of rabbits identified quantitative and qualitative differences in terms of the functional IgG antibody response against the P. falciparum parasite. The antibodies induced by one protein variant were shown to be qualitatively similar to responses induced by other vaccine platforms. This work identifies Drosophila S2 cells as a clinically-relevant platform suited for the production of 'difficult-to-make' proteins from Plasmodium parasites, and identifies a PfRH5 sequence variant that can be used for clinical production of a non-glycosylated, soluble full-length protein vaccine immunogen.